Elemental and lattice-parameter mapping of binary oxide superlattices of (LaNiO3)4/(LaMnO3)2 at atomic resolution. (19th December 2016) - Kwon, Ji-Hwan; Lu, Ping; Hoffman, Jason; Yuan, Renliang; Yoon, Aram; Bhattacharya, Anand; Zuo, Jian-Min
Abstract: We construct the elemental distribution and lattice strain maps from the measured atomic column positions in a (LaNiO3 )4 /(LaMnO3 )2 superlattice over a large field of view. The correlation between the distribution of B-cations and the lattice parameter in the form of Vegard's law is validated using atomic resolution energy dispersive x-ray spectroscopy (EDS). The maps show negligible Mn intermixing in the LaNiO3 layer, while Ni intermixing in the LaMnO3 layer improves away from the substrate interface to 9.5 atomic% from the 8th period onwards, indicating that the superlattice interfacial sharpness is established as the distance from the substrate increases. The maps allow an observation of the compositional defects of the B-sites, which is not possible by Z-contrast alone. Thus, this study demonstrates a promising approach for atomic scale correlative study of lattice strain and composition, and a method for the calibration of atomic resolution EDS maps.